Experimental study of volatile organic compounds catalytic combustion on Cu‐Mn catalysts with different carriers. (18th January 2021) - Guo, Mingnv; Fang, Ruiming; Liu, Xianwei; Yang, Zhongqing
Summary: Catalytic combustion is an effective way for volatile organic compounds harmless treatment. In this paper, the synergism between non‐noble metal active phase Cu‐Mn and Y‐zeolite, SiO2, γ‐Al2 O3, and TiO2 was studied by catalytic combustion experiments and corresponding characterizations; the conclusions as following: Cu‐Mn/SiO2 has the best activity and stability, T10 and T90 are 210°C and 298°C, respectively. Benzene can be completely oxidized below 300°C, which is due to the formation of substantial Cu‐Mn solid solutions and a large number of Cu 2+ /Mn 3+ ions on the surface of SiO2 . The activation energy of C6 H6 in CuMn2 /TiO2 is 95.50 kJ/mol, while that of the other three catalysts is close, probably 60 kJ/mol. Moreover, the stability of SiO2 is the highest and can be maintained for more than 60 hours. The fundamental reason of catalyst deactivation is the higher diffusion resistance on the surface of the catalyst with small pore size distribution and the lack of surface oxygen, which leads to the lower degree of complete oxidation of C6 H6 . Abstract : The CuMn2 /SiO2 and CuMn2 /Y‐Zeolite exhibit the excellent activity for the catalytic oxidation of VOCs, while the former has the best adaptability over a wide concentration range and the best stability. The mechanism of the effect of four different carriers on the activity of Cu‐Mn catalyst and the fundamental reason of catalyst deactivation were thoroughly investigated through characterization techniques and the kinetic calculation of catalytic reaction.